The Effect Of Price And Service Quality On Consumer Decisions At The Minang Pangkalan Balai Gold Shop, Banyuasin Regency - Melisa Melisa; Erfan Robyardi; Erdiansyah Erdiansyah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of price, service quality, and consumer decisions (Y) at the Usaha Minang Gold Shop, Pangkalan Balai, Banyuasin Regency. The research method used is a quantitative method with an associative approach. This study involved 79 respondents who were consumers of the Usaha Minang Gold Shop. Data collection techniques were carried out through questionnaires that had been tested for validity and reliability. Data analysis used classical assumption tests (normality, multicollinearity, and heteroscedasticity), as well as multiple linear regression analysis, t-test, and F-test. The results of the t-test (partial) showed that the Price variable had a significant effect on consumer decisions, with a significant value of 0.000 (<0.05). The service quality variable also had a significant effect on consumer decisions, with a significant value of 0.046 (<0.05). In addition, the results of the F-test (simultaneous) showed that Price and service quality together had a significant effect on consumer decisions (Y). with a significant value of 0.000 (0.05).